2013
DOI: 10.1590/s0034-72802013000500013
|View full text |Cite
|
Sign up to set email alerts
|

Kabuki Syndrome: a case report with severe ocular abnormalities

Abstract: Kabuki syndrome is a rare congenital anomaly, characterized by five fundamental features, the "Pentad of Niikawa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…Refractive errors, nystagmus, corneal pannus, caruncle lipoma (Evans et al, 2004) and prepapillary gliosis (Chuah et al, 2009) have also been reported. Microphthalmia, microcornea and colobomata have also been identified previously in patients with Kabuki syndrome (Kluijt et al, 2000;Turner et al, 2005;Chaudhry et al, 2008;Medina et al, 2013;Patel and Alkuraya, 2015). The typical mid-brow deficiency and lower lid ectropion of Kabuki syndrome can be seen in addition to bilateral anophthalmia.…”
Section: Discussionsupporting
confidence: 53%
“…Refractive errors, nystagmus, corneal pannus, caruncle lipoma (Evans et al, 2004) and prepapillary gliosis (Chuah et al, 2009) have also been reported. Microphthalmia, microcornea and colobomata have also been identified previously in patients with Kabuki syndrome (Kluijt et al, 2000;Turner et al, 2005;Chaudhry et al, 2008;Medina et al, 2013;Patel and Alkuraya, 2015). The typical mid-brow deficiency and lower lid ectropion of Kabuki syndrome can be seen in addition to bilateral anophthalmia.…”
Section: Discussionsupporting
confidence: 53%
“…These are defined as characteristic facial appearance, extremity and skeletal anomalies, dermatoglyphic abnormalities, mental retardation, and postnatal growth retardation. [1][2][3] It has been reported that most KS cases in the literature were diagnosed with a typical facial appearance. KS is often sporadic and most of the patients have a negative family history.…”
Section: Introductionmentioning
confidence: 99%